Multidimensional poverty and inclusive growth in India: an analysis using growth elasticities and semi-elasticities - Seth, S; Alkire, S (Emerald, 2021)
Post reform India has generated high economic growth, yet progress in income poverty and many other key development outcomes has been modest. This chapter primarily examines how inclusive economic growth has been in India between 2005–2006 and 2015–2016 in reducing multidimensional poverty captured by the global multidimensional poverty index (MPI). The authors employ a constellation of elasticity and semi-elasticity measures to examine vertical, horizontal as well as dimensional inclusiveness of economic growth. Nationally, the authors estimate that a 1% annual economic growth in India during their study period is associated with an annual reduction in MPI of 1.34%. The association of the national growth to state poverty reduction (horizontal inclusiveness) is, however, not uniform. Some states have been successful in reducing poverty faster than the national average despite slower economic growth between 2005–2005 and 2015–2016; whereas, other states have been less successful to do so despite faster economic growth during the same period. The authors’ analyses and findings show how these tools may be used in practical applications to measure inclusive growth and inform policy.